EMPLOYEE PERCEPTIONS OF ORGANIZATIONAL CULTURE IN THE DEPARTMENT OF EDUCATION AND CULTURE OF AGAM REGENCY - Astuti, Meliza; Santoso, Yulianto; Ermita; Achyar, Novriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the phenomenon that organizational culture at the Education and Culture Office of Agam Regency had not been implemented optimally. This was indicated by the lack of employee independence in carrying out tasks, suboptimal time discipline, insufficient teamwork among employees, and inconsistent work discipline. The purpose of this study was to determine employees’ perceptions of organizational culture at the Education and Culture Office of Agam Regency in terms of professionalism, commitment, teamwork, and work discipline. This study employed a quantitative approach with a descriptive research method. The population consisted of 79 employees, including civil servants, government employees with work agreements (PPPK), and non-civil servant employees. The sample comprised 68 respondents selected using the proportional random sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using mean score analysis. The results showed that employees’ perceptions of organizational culture at the Education and Culture Office of Agam Regency were categorized as good, with an average score of 3.85 for professionalism, 4.27 for commitment, 4.19 for teamwork, and 4.17 for work discipline. Among the four indicators, commitment obtained the highest average score, while professionalism obtained the lowest. Overall, the organizational culture at the Education and Culture Office of Agam Regency has been implemented well; however, improvements are still needed, particularly in the aspect of professionalism, to support the achievement of organizational goals more effectively.